2012
DOI: 10.1371/journal.pone.0044331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rheumatoid Arthritis Subtypes Using Symptom Profiles, Clinical Chemistry and Metabolomics Measurements

Abstract: ObjectiveThe aim is to characterize subgroups or phenotypes of rheumatoid arthritis (RA) patients using a systems biology approach. The discovery of subtypes of rheumatoid arthritis patients is an essential research area for the improvement of response to therapy and the development of personalized medicine strategies.MethodsIn this study, 39 RA patients are phenotyped using clinical chemistry measurements, urine and plasma metabolomics analysis and symptom profiles. In addition, a Chinese medicine expert clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 55 publications
1
71
0
Order By: Relevance
“…A Dutch group looked at RA subtypes using clinical chemistry measurements, urine and plasma LC-MS metabolomics analysis and according to traditional Chinese medicine (TCM) theory. They showed that urine acylcarnitines could separate patients into heat and cold Chinese medicine RA subtypes and hypothesized that the acylcarnitines could be related to fatigue levels in the patients and suggested that carnitine and acylcarnitine supplementation might be beneficial in the cold patient subtypes [92]. Of note, recent metabolic phenotyping of atherosclerotic plaques showed perturbations in acylcarnitine metabolism which the authors suggest is related to dysregulation of fatty acid metabolism and mitochondrial dysfunction [93••].…”
Section: Metabolomics In Ramentioning
confidence: 99%
“…A Dutch group looked at RA subtypes using clinical chemistry measurements, urine and plasma LC-MS metabolomics analysis and according to traditional Chinese medicine (TCM) theory. They showed that urine acylcarnitines could separate patients into heat and cold Chinese medicine RA subtypes and hypothesized that the acylcarnitines could be related to fatigue levels in the patients and suggested that carnitine and acylcarnitine supplementation might be beneficial in the cold patient subtypes [92]. Of note, recent metabolic phenotyping of atherosclerotic plaques showed perturbations in acylcarnitine metabolism which the authors suggest is related to dysregulation of fatty acid metabolism and mitochondrial dysfunction [93••].…”
Section: Metabolomics In Ramentioning
confidence: 99%
“…(56,57) These types of RCTs include patients according to their genotype rather than the traditional methods based on clinical diagnosis. This personalized medicine may be corresponding well to individualized diagnostic and individualized treatment concept of traditional Asia medicine, i.e., Van, et al (58)(59)(60) study showed that "heat" and "cold", two Chinese medicine diagnosis patterns, was associated with different underlying genomic and metabolomics profiles and different treatment outcomes. Thus sponsor and PI need to consider alternative therapeutic endpoint for RCTs design, redesigning RCTs may integrate traditional herbal medicinal approaches to conventional Western medicine.…”
Section: Clinical Trial Designmentioning
confidence: 92%
“…This has revealed shared profiles of overexpressed miRNAs but it is the signature measurable in blood including miR-24, miR-125a-5p, and miR-451, amongst others, that holds the most promise as biomarkers [104][105][106][107][108][109] . Recent work provided evidence for the use of 14-3-3n serum antibodies in RA 110,111 , and a diagnostic blood panel (including ANA, anti-Ro, anti-La, rheumatoid factor, and novel SjS autoantibodies such as anti-salivary gland protein 1 (SP1), anti-carbonic anhydrase 6 (CA6) and anti-parotid secretory protein (PSP)) for Sjögren syndrome [112][113][114] .…”
Section: Autoimmunitymentioning
confidence: 99%